High-Density Lipoprotein, Mean Platelet Volume, and Uric Acid as Biomarkers for Outcomes in Patients With Sepsis: An Observational Study. (July 2020) - Montero-Chacón, Luis Bolívar; Padilla-Cuadra, Juan Ignacio; Chiou, Sy Han; Torrealba-Acosta, Gabriel
Background: We conducted an observational study evaluating the association between uric acid, mean platelet volume (MPV), and high-density lipoprotein (HDL) with complications and outcomes of patients with sepsis in a critical care setting. Methods: We followed patients with a diagnosis of severe sepsis and septic shock for a maximum of 28 days. Main outcomes assessed included length of stay (LOS), the need for renal replacement therapy (RRT), assisted mechanical ventilation (AMV), and vasopressor support as well as in-unit mortality. Results: The overall average age of the 37 patients enrolled was 48.1 (19.8) years; among them, 37.8% were male. Abdominal related (43.2%) and pulmonary (29.7%) were the main sites of infection. The overall Acute Physiology and Chronic Health Evaluation 2 (APACHE-2) median score was 19 (9-24). Acute kidney injury (AKI) was observed in 46.9% of the sample. In all, 54.1% required vasopressor support, 54.1% AMV, and 35.1% RRT. Patients with bacteremia were significantly more likely to require vasopressor support and those with urinary tract infections were significantly younger. We found increasing ΔMPV levels, higher APACHE-2 scores, lower HDL values, and a reduced age to be associated with a longer LOS. Higher scores on the APACHE-2 scale and lower levels of HDL significantly associated with higher odds for developing AKI. The need for vasopressor support was significantly associated with higher values of 72-hour MPV and with higher levels of baseline uric acid and lower values of initial HCO3 . Initial and 72-hour levels of MPV and higher scores in the APACHE-2 were all significantly correlated with the need for AMV. An increased probability of dying during follow-up was significantly correlated with increasing age. Conclusion: We were able to establish significant associations between our candidate biomarkers and relevant outcomes for patients with sepsis. Our results support the use of these low-cost biomarkers in the assessment of prognosis of patients with sepsis.